Memorandum of Understanding between the Elsevier Foundation and Aysha Abed Library, Brac University (2009) ﻿ ﻿ - The Elsevier Foundation; Aysha Abed Library, Brac University (The Elsevier Foundation and Aysha Abed Library, Brac University, 2019)
The agreement made between Elsevier Foundation and Ayesha Abed Library, Brac University for establishing an integrated library system at Brac University.